Evaluating The Rise of People Risk: An Empirical Investigation Of The Financial Services Industry - Ighoyota-Amori, Eseoghene Glorienta (2016)
Over the past 20 years, the financial services industry has been in the eyes of the media as a result of the huge amount of financial losses and failures. Many financial institutions such as Barings bank and even the famous case of the global financial crisis have all undergone massive loss events due to fraudulent activities and incompetency. Whilst majority of research has been focused on dealing with credit and market risk not much has been done to properly tackle operational risk despite Basel contributions in this field. However, a large focus has been on the behavioural aspect and processes of the issue and thus the novel term ‘people risk’ has emerged. This became an important topic area within the financial services industry to properly manage operational risk, as people were found to be a fundamental element and possibly root cause of these loss events, thereby enabling a point of reference for better prevention and people risk management. This paper facilitated a qualitative content analysis that explored 20 Final notices over the course of three years issued by the FCA with regulatory fines around £2,000,000 and above from 2013-2015. This was done in order to ascertain common themes around the loss events of the financial institution that can better improve the understanding. The use of the risk culture treating customer fairly framework will be used as a foundation to categorised the common issues found and therefore the GFC period and post–crisis period will be compared and contrasted to better analysis and thus serve as a starting point for people risk management framework.